Introducing stratigraphy - Lyle, Paul (Introducing Earth and environmental sciences., 2019)
The extraordinary and beautiful scenery of the Northern Scottish Highlands has been created by a geological history lasting over 3 billion years. This is an illustrated geological history of those years, showing the rocks, visiting the places and introduces famous researchers and their theories that have been inspired by the Highlands